Computational validation of the design of an air-biogas mixer for a turboalimented diesel engine - Carpintero Durango, Javier; Fábregas Villegas, Jonathan; Santamaría De La Cruz, Henry; Pérez Pérez, Saul; Valencia Ochoa, Guillermo (International Journal of Engineering and Technology, 2019)
The design of two air-biogas mixers according to the design literature of these devices for Diesel engine applications was studied through computational fluid dynamics (CFD). The gradient of hydrodynamic variables was profiled on the longitudinal axis of the compared equipment. This research presents a comparison instrument about the efficiency of the design methodology for sizing gaseous fuel air mixing equipment. Comparing the design methodologies of Agudelo and Mitzlaff mixing tubes, the profiles of velocities, pressure profiles and volumetric fraction profiles of the mixtures were obtained.